Post-conflict acute stress reactions in Kazakhstan in the aftermath of January 2022 unrests: A national survey - Natalya Glushkova; Alexandr Ivankov; Varvara Trenina; Ainash Oshibayeva; Zhanna Kalmatayeva; Zhanar Temirbekova; Saltanat Mamyrbekova; Kairat Davletov; Zaituna Khismetova; Almagul Kauysheva; Ardak Auyezova; Marat Zhanaspayev; et al. (Heliyon, 2023)
Background: In January 2022 Kazakhstan experienced unprecedented nationwide protests that quickly turned to violent riots. Although the number of individuals affected physically by the disturbances were cited, the emotional toll of the events remains undetermined. The aim of this study was to evaluate the comparative rates of acute stress reactions in Kazakhstan in the aftermath of the unrests. Methods: A cross-sectional, population-based online survey was conducted one month after the start of the disturbances. The study questionnaire were completed anonymously and included the Primary Care PTSD Screen for DSM-5 (PC-PTSD-5) and the General Anxiety Disorder-7 (GAD-7), as well as socio-demographic and event exposure information. Results: Of the 7021 people who initially agreed to participate, 6510 were able to complete the full survey. For a cut-off of ≥3 on the PC-PTSD-5, 14.8 % of the study participants exhibited symptoms. With a cut-off of ≥4, this percentage reduced to 4.6 %. Participants from Almaty city and Almaty region who experienced the most extensive disturbances showed a doubled prevalence compared to the national level (30.0 % for a cut-off of ≥3, and 10.1 % for a cut-off of ≥4). At the national level, the prevalence of anxiety symptoms, defined as a score of ≥10 on the GAD-7, stood at 10.9 %. This prevalence decreased to 4.2 % when considering a cut-off of ≥15. Conclusion: Health authorities of riot-affected areas ought to be aware of the population level mental health impact of the civil conflict and consider provision of targeted interventions to mitigate the long-term consequence of these lifespan disorders, while also seeking for the peaceful resolution of the ensuing conflicts.